The Judgement of Paris as Examined by a Lawyer and a Christian Moralist: Dracontius’ De raptu Helenae - Cichoń, Natalia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
In this paper I examine Dracontius’ poem De raptu Helenae to prove his unconventionality and originality in presenting a well-known myth. He analyses the story of the judgement of Paris from the legal point of view using professional, legal vocabulary. At the same time he takes into account also the moral and Christian dilemmas and thereby he finds completely new aspects and interpretations, ignored by previous poets.